EDUCATIONAL VALUES IN THE QUR'AN SURAH AT-TAHRIM - Timbul Arafah Munthe; Fahrurrozi S (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
In the Qur'an, Allah SWT not only commands us to protect ourselves from the torment of hellfire, but Allah SWT also commands us to protect our families from the torment of hellfire This research is a qualitative research with the type of library study (library reseach) the author tries to examine the value of education in the Qur'an letter at-tahrim. The method used in this research is descriptive method with the aim to describe systematically and precisely about the educational values contained in the Qur'an. The research technique used is literature study, namely reading, understanding, analyzing supporting books. This research is a qualitative research with the type of library study (library reseach) the author tries to examine the value of education in the Qur'an letter at-tahrim. The method used in this research is descriptive method with the aim to describe systematically and precisely about the educational values contained in the Qur'an.. The results of this study indicate that the values contained in the Qur'an letter at tahrim are: a). Believe in allah swt with true faith. b). Believe in the existence of the Day of Judgment. c). Protect yourself and your family from the torment of hellfire. d). Worship. e). Example of a good wife